Analysis of Sukuk Default from the Perspective of the Principle of Al-Ghunmu bil Ghurm and Sharia Asset Guarantee Mechanisms - Nur Syarifatul Isra; Husni Husni (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
The rapid development of sukuk within contemporary Islamic capital markets has generated critical debate regarding the consistency between the theoretical foundations of Islamic finance and the practical implementation of sukuk structures, particularly in cases of issuer default and bankruptcy. This study aims to analyze sukuk default from the perspective of the principle of al-ghunmu bil ghurm and sharia asset guarantee mechanisms. This research employs a qualitative library research design using a normative-doctrinal approach. The data were collected from DSN-MUI fatwas, classical fiqh mu‘āmalah literature, sukuk prospectuses, bankruptcy regulations, and contemporary scholarly publications related to Islamic finance and sukuk default. The collected data were analyzed using descriptive-analytical and content analysis methods. The findings reveal that contemporary sukuk structures have experienced a substantial transformation from substantive risk-sharing mechanisms toward risk-transfer arrangements through the widespread use of purchase undertaking clauses, principal repayment guarantees, and liquidity support facilities. The study further demonstrates that the dominance of asset-based sukuk creates significant legal fragility because investors generally possess only beneficial ownership rights that are not legally enforceable during bankruptcy proceedings. Consequently, underlying assets frequently fail to function as effective legal protection mechanisms for investors. This study also identifies the emergence of a “Shariah Compliance Paradox,” namely the coexistence of formal sharia compliance with substantive financial practices that reproduce conventional debt-based logic. The study concludes that contemporary sukuk practices increasingly prioritize market competitiveness and investor certainty at the expense of substantive Islamic principles of distributive justice and equitable risk sharing. Therefore, stronger sharia governance, regulatory reform, and the gradual standardization of asset-backed sukuk structures are necessary to preserve the authenticity and credibility of Islamic finance.